2021
DOI: 10.3389/fimmu.2021.658428
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein Suppresses ACE2 and Type I Interferon Expression in Primary Cells From Macaque Lung Bronchoalveolar Lavage

Abstract: SARS-CoV-2 virus causes upper and lower respiratory diseases including pneumonia, and in some cases, leads to lethal pulmonary failure. Angiotensin converting enzyme-2 (ACE2), the receptor for cellular entry of SARS-CoV-2 virus, has been shown to protect against severe acute lung failure. Here, we provide evidence that SARS-CoV-2 spike protein S1 reduced the mRNA expression of ACE2 and type I interferons in primary cells of lung bronchoalveolar lavage (BAL) from naïve rhesus macaques. The expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 62 publications
3
30
1
3
Order By: Relevance
“…Consistent with our findings, it was recently reported that recombinant SARS-CoV-2 Spike protein, when incubated with primary cells from lung bronchoalveolar lavage from rhesus macaques, was able to suppress IFN-I levels ( Sui et al., 2021b ). Our data, in part, attempts to uncover the mechanism by which Spike suppresses the IFN-I response by revealing that SARS-CoV-2 Spike targets the IRF3 transcription factor.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, it was recently reported that recombinant SARS-CoV-2 Spike protein, when incubated with primary cells from lung bronchoalveolar lavage from rhesus macaques, was able to suppress IFN-I levels ( Sui et al., 2021b ). Our data, in part, attempts to uncover the mechanism by which Spike suppresses the IFN-I response by revealing that SARS-CoV-2 Spike targets the IRF3 transcription factor.…”
Section: Discussionsupporting
confidence: 93%
“…Given the fact that SARS-CoV-1 and SARS-CoV-2 both rely on the binding of the viral S glycoprotein to ACE2 for viral entry into cells it was therefore highly likely that ACE2 would also be downregulated by SARS-CoV-2 in COVID-19. This has now been confirmed by Lei et al (2021) [31], Pedrosa et al (2021) [32] and Sui et al (2021) [33]. For example, Pedrosa et al (2021) showed that the S protein can cause a 50% reduction in the 120KDa membrane-bound form of ACE2 in human alveolar type 2 A549 cells.…”
Section: The Role Of Ace2 In the Raas And Kksmentioning
confidence: 74%
“…Although unmodified mRNA vaccines increase ISGs in both control and AGS samples, the internalization of the nucleoside modified mRNA vaccine representing the clinical vaccine significantly decreases ISGs relative to untreated samples in both control and AGS samples. It should be noted that the SARS-CoV-2 spike protein itself has been shown in vitro to result in decreased production of type 1 IFN [30], but that SARS-CoV-2 overall has a complex interaction with IFNs, likely associated with tissue specificity and disease severity [18, 29, 31]. It is promising that the expression of RNA sensing genes is upregulated only in the presence of unmodified mRNA vaccine, as expected.…”
Section: Discussionmentioning
confidence: 85%